Bayesian Analysis Toolkit: 1.0 and beyond. Issue 7 (December 2015) - Beaujean, Frederik; Caldwell, Allen; Greenwald, D.; Kluth, S.; Kröninger, Kevin; Schulz, O.
Abstract: The Bayesian Analysis Toolkit is a C++ package centered around Markov-chain Monte Carlo sampling. It is used in high-energy physics analyses by experimentalists and theorists alike. The software has matured over the last few years. We present new features to enter version 1.0, then summarize some of the software-engineering lessons learned and give an outlook on future versions.